Coordinated Control of PSS with Type-2 Fuzzy Lead Lag SSSC Damping Controller Design Using Modified Local Signal - Patra , Asit Kumar; Keshori Mohapatra, Sangram (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2023)
The Sine Cosine adapted improved WOA(SCiWOA) based design coordinated control of Type-2 fuzzy logic control (T2FLC) power system stabilizer (PSS) with modified local signal (MLS) input to Type-2 FLC lead-lag-based Static synchronous Series Compensator (SSSC) controller considered for transient stability improvement. Initially, the SCiWOA optimized coordinated control of MLS input to a lead lag-based SSSC controller with PSS was compared with the Whale Optimization Algorithm (WOA) and particle swarm optimization (PSO) based coordinated control of the same controller with the structure of the SMIB power system. It is seen from the demonstration that improvements in the ITAE error with the proposed SCiWOA tuned compared to WOA and PSO are 29.83% and 33.91%, respectively. The different input signals to PSS and SSSC coordinated control were verified to check the effectiveness and robustness of the analysis of the transient stability of the power system. The next part of the analysis attempted to coordinate the control of T2FLC based PSS with a T2 FLC controller with a remote input signal (Δ𝜔) based PSS with a lead-lag SSSC damping controller under different loading and fault conditions of the SMIB power system. Lastly, the effectiveness of the proposed coordinated controller demonstrated in three machine power systems shows that the proposed T2FLC based PSS with MLS input-based T2FLC in the SSSC damping controller has superior transient performance as compared with PSS with MLS input to the SSSC controller and PSS with MLS input to the SSSC controller under three different contingencies of the power system.